2021
DOI: 10.21203/rs.3.rs-651878/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Metagenomic Insights Into Co-Proliferation of Vibrio Spp. and Dinoflagellates Prorocentrum During A Spring Algal Bloom in the Coastal East China Sea Near Xiamen

Abstract: BackgroundCoastal harmful algal blooms (HAB), commonly termed ‘Red tides’, have severe undesirable consequences to the marine ecosystems and local fishery and tourism industries. Increase in nitrogen and/or phosphate loading is often attributed as the major culprits of increasing frequency and intensity of the coastal HAB; however, fundamental understanding is lacking as to the causes and mechanism of bloom formation despite decades of intensive investigation.ResultsIn this study, we interrogated the prokaryot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…A study on P. donghaiense found that as P. donghaiense is primarily a photoautotrophic organism with carbon needs mostly fulfilled from uptake of inorganic carbon, the environmental factors regarded to be crucial to its overgrowth during the bloom events are presumably availability of nitrogen and phosphorus, as suggested by previous laboratory observations (Varkitzi et al, 2010;Anderson et al, 2012). Kim et al (2021) found through their study on the co-proliferation of Vibrio spp. and dinoflagellates Prorocentrum during a spring algal bloom in the coastal East China Sea that there is a clear correlation between Vibrio and algal blooms.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…A study on P. donghaiense found that as P. donghaiense is primarily a photoautotrophic organism with carbon needs mostly fulfilled from uptake of inorganic carbon, the environmental factors regarded to be crucial to its overgrowth during the bloom events are presumably availability of nitrogen and phosphorus, as suggested by previous laboratory observations (Varkitzi et al, 2010;Anderson et al, 2012). Kim et al (2021) found through their study on the co-proliferation of Vibrio spp. and dinoflagellates Prorocentrum during a spring algal bloom in the coastal East China Sea that there is a clear correlation between Vibrio and algal blooms.…”
Section: Discussionmentioning
confidence: 80%
“…Water eutrophication can easily lead to the occurrence of anaerobic environments, and therefore, the population size of sulfate-reducing bacteria can to some extent indicate the level of water nutrient enrichment. Existing studies have shown that in general, the abundance of sulfate-reducing bacteria is negatively correlated with dissolved oxygen content and positively correlated with water nutrient enrichment (Kim et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation